You first inspire your team to grow up, get along, and get stuff done - Davey, Liane (Gildan Audio, 2020)
Team dysfunctions are discouragingly prevalent throughout most businesses as there are so many ways a team can go wrong. Sometimes the results of team dysfunction are relatively innocuous. The team might just be a little slower or a little less rewarding than you would like.' But in too many teams, the problems are more severe.' People find themselves dreading a job they used to enjoy because their teammates are bickering, or rejecting new ideas, or simply not pulling their weight. This book presents new ideas and processes for increasing team effectiveness. The author proposes that a healthy team needs two basic things: first, team members need to bring diverse talents and perspectives into alignment around the unique value they can add for the organization. Second, they need to trust each other enough to engage in productive conflict. The book addresses the 5 most common ways in which teams become toxic and destroy any chance of creating the value the organization is counting on them to produce.' Then, it spells out the antidotes to those dysfunctions that will protect teams from self-destructing.' Finally, it concludes by instructing team members on the language they can use to begin to change their team.' Designed for front line employees, middle managers, executives teams, or anyone who works regularly in teams, the book helps you figure out how to make your team more productive.'